Pengembangan Media Pembelajaran Interaktif Berbasis Teknologi Informasi dalam Meningkatkan Pemahaman Konsep Matematika Siswa Smp Kelas VII Pada Materi Aritmatika Sosial - Diana Lutfiah Nur Ramadhani; Oktavia Damayanti; Cahyani Ayu Anggreini; Dina Noviyanti; Aisyah Cheren Laurensa; Dyana Wijayanti (Journal on Education, 2023)
Understanding mathematical concepts is an important key in learning mathematics. However, students often have difficulty understanding mathematical concepts, especially social arithmetic material. Based on this, this research aims to develop information technology-based interactive learning media that can help improve understanding of mathematics concepts for class VII middle school students in social arithmetic material. This research was conducted at SMP Negeri 1 Kalinyamatan involving 34 class VII junior high school students. The research method used is Research and Development (R&D) using the ADDIE Model design. The results of data analysis show that interactive learning media is proven to be valid because it has a significant level of 0.00 < 0.05, feasible because all variables (statements) have a calculated r value > r table and is effective because it meets the individual due diligence and classical due diligence, so it can It is said that the development of interactive learning media based on information technology which was developed is effective in increasing understanding of mathematics concepts for class VII middle school students in social arithmetic material. The evaluation results show that students' understanding of mathematical concepts has increased significantly after using interactive learning media.